PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA KELAS VIII DI SMP NEGERI 5 KOTA BENGKULU - Intan Anggriani; khermarinah; Randi (IKIP Siliwangi, 2026)
This study aims to determine the effect of the Inquiry learning model on student achievement in Indonesian language in eighth grade at SMP Negeri 5, Bengkulu City, consisting of two classes. This study is categorized as a quantitative quasi-experimental study using the